2004
DOI: 10.1074/jbc.m311780200
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1 Phosphorylation by Aurora-A in the Regulation of G2 to M Transition

Abstract: Aurora-A/BTAK/STK15 localizes to the centrosome in the G2-M phase, and its kinase activity regulates the G2to M transition of the cell cycle. Previous studies have shown that the BRCA1 breast cancer tumor suppressor also localizes to the centrosome and that BRCA1 inactivation results in loss of the G2-M checkpoint. We demonstrate here that Aurora-A physically binds to and phosphorylates BRCA1. Biochemical analysis showed that BRCA1 amino acids 1314–1863 binds to Aurora-A. Site-directed mutagenesis indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(90 citation statements)
references
References 53 publications
4
82
0
1
Order By: Relevance
“…Interestingly, it was recently shown that Aurora-A physically binds and phosphorylates BRCA1 at S308, and the phosphorylation is correlated with impaired function of BRCA1 in regulating G2/M transition (Ouchi et al, 2004). Altogether, these findings suggest a link between Aurora-A overexpression and impaired BRCA1 function in genetic instability and tumorigenesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, it was recently shown that Aurora-A physically binds and phosphorylates BRCA1 at S308, and the phosphorylation is correlated with impaired function of BRCA1 in regulating G2/M transition (Ouchi et al, 2004). Altogether, these findings suggest a link between Aurora-A overexpression and impaired BRCA1 function in genetic instability and tumorigenesis.…”
Section: Discussionmentioning
confidence: 94%
“…The phosphorylation of these sites is responsible for the inactivation of p53 transactivation activity and degradation of p53, respectively Liu et al, 2004). It was recently shown that Aurora-A physically binds and phosphorylates BRCA1 at S308 (Ouchi et al, 2004). This phosphorylation is correlated with progression of cells from the G2 phase to the M phase, while BRCA1-S308N, a form that cannot be phosphorylated by Aurora-A, behaves like wild-type BRCA1 in reducing number of cells in the M phase when expressed in BRCA1-deficient mouse embryo fibroblasts (MEFs).…”
Section: Introductionmentioning
confidence: 99%
“…mobility intermediate to those of the hyper-and hypophosphorylated BRCA1 species detectable at other cell cycle stages (lanes 1 and 3). The BRCA1 polypeptides of mitotic cells presumably bear a distinctive pattern of post-translational modifications distinct from those of the hypo-and hyperphosphorylated BRCA1 (48). If the hypophosphorylated forms of BRCA1 are indeed more susceptible to proteasomal degradation, then the absence of these forms in prometaphase may explain why ubiquitination of BRCA1 is reduced at this stage of the cell cycle (Fig.…”
Section: Bard1 Expression Stabilizes Exogenous Brca1 By Specifically mentioning
confidence: 99%
“…Aurora kinases have already been shown to phosphorylate a number of different substrates. Specifically, Aurora A phosphorylates TPX2, LIM protein, CDC25B, p53, BRCA1, ASAP, and others (7)(8)(9)(10)(11)(12)(13), whereas Aurora B phosphorylates histone H3, MCAK, histone H2A, topoisomerase II, INCENP, survivin, and CENP-A (14 -20).…”
mentioning
confidence: 99%